Adaptive capabilities of the circulatory system in children diagnosed with glomerulonephritis - Kundina , Viktoriia; Storozhchuk, Yuliia; Medvediev, Volodymyr (Journal of Education, Health and Sport, 2024)
Introduction.Glomerulonephritis (GN) is characterised by a polysystemic lesion and early involvement of the cardiovascular system (CVS) in the overall pathological process. Cardiovascular lesions in patients with GN are primarily going with the presence of arterial hypertension syndrome and varying degrees of circulatory failure. Aim of the study. Determination of the peculiarities of circulatory system adaptation in children with GN with nephrotic syndrome (NS) using ultrasound with doppler assessment of intracardiac flow. Materials and methods of research. 50 children were diagnosed with acute GN (AGN) with NS, and 100 patients were diagnosed with nephrotic form (NF) of chronic GN (CGN). The control group consisted of 30 practically healthy children. Echocardiography was performed on a combined ultrasound system GE with a special cardiological programme for cardiac examination in M-, B- and Doppler modes using a mechanical sectoral transducer of 3.5 MHz. Echocardiography was performed from the parasternal position along the long axis of the heart. In this case, the transducer was placed to the left of the sternum in 3 to 4 intercostal spaces and the central ultrasound beam was directed perpendicular to the surface of the chest. Echocardiography was used to determine the main haemodynamic parameters: ejection fraction (EF), minute blood volume (MBV), cardiac index (CI), velocity parameters of transmitral (TMK) and transaortic (TAK) blood flows according to the standard method [1]. The echocardiography method was used in 150 children. The average age of the subjects was 8.2 ± 1.3 years. Results. Hypokinetic and hyperkinetic circulation types were found with equal frequency (42.8%) in 12 patients with AGN. In CGN, a different picture was observed: 11 patients had a normokinetic type of blood circulation (40.7%), while hypokinetic was found in 9 patients (33.3%) and hyperkinetic in 7 patients (26%). The normokinetic type of hemodynamics at the second stage was observed in 4 patients (19.1%) with AGN and in 19 patients (51.4%) with CGN. The percentage of patients with a hypokinetic type of hemodynamics decreased in the case of AGN from 42.8% to 33.3%; in the case of CGN - from 33.3% to 16.2%. In 36 patients with chronic GN after completion of GC and CS therapy, the predominant type of haemodynamics was normokinetic, which was observed in 22 patients (61.2%), hypokinetic and hyperkinetic types of circulation were diagnosed in 14 patients (19.4%, respectively). Conclusion: In case of CGN, before treatment, hyperkinetic and hypokinetic types of haemodynamics prevail, and after treatment discontinuation, the hypokinetic type slightly prevails, and hyper- and normokinetic types of haemodynamics occur with equal frequency, indicating heterogeneity of adaptive reactions of the cardiovascular system.